Researching networks and collaboration in the public sector : a guide to approaches, methodologies and analytics - Voets, Joris; Keast, Robyn; Koliba, Christopher (London : Routledge, 2018)
Networks and other collaborations are central to the public sector's ability to respond to their diverse responsibilities, from international development and regional governance, to policy development and service provision. Great strides have been made toward understanding their formation, governance and management, but more opportunities to explore methodologies and measures is required to ensure they are properly understood. This volume showcases an array of selected research methods and analytics tools currently used by scholars and practitioners in network and collaboration research, as well as emerging styles of empirical investigation. Although it cannot attempt to capture all technical details for each one, this book provides a unique catalogue of compelling methods for researchers and practitioners, which are illustrated extensively with applications in the public and non-profit sector. By bringing together leading and upcoming scholars in network research, the book will be of enormous assistance in guiding students and scholars in public management to study collaboration and networks empirically by demonstrating the core research approaches and tools for investigating and evaluating these crucially important arrangements.
OCLC-licensed vendor bibliographic record.
Keywords: Public administration; Business networks; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Nonprofit Organizations & Charities; POLITICAL SCIENCE / Public Affairs & Administration